Comparison of 30-Day Morbidity and Mortality After Arthroscopic Bankart, Open Bankart, and Latarjet-Bristow Procedures: A Review of 2864 Cases. Issue 7 (3rd July 2017) - Bokshan, Steven L.; DeFroda, Steven F.; Owens, Brett D.
Background: Surgical intervention for anterior shoulder instability is commonly performed and is highly successful in reducing instances of recurrent instability. Purpose: To determine and compare the incidence of 30-day complications and patient and surgical risk factors for complications for arthroscopic Bankart, open Bankart, and Latarjet-Bristow procedures. Study Design: Cohort study; Level of evidence, 3. Methods: All arthroscopic Bankart, open Bankart, and Latarjet-Bristow procedures from 2005 to 2014 from the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) prospective database were analyzed. Baseline patient variables were assessed, including the Charlson Comorbidity Index (CCI). Outcomes measures included length of operation, length of hospital stay, need for hospital admission, 30-day readmission, and 30-day return to the operating room. Binary logistic regression was performed for the presence of any complications after all 3 procedures. Results: There were 2864 surgical procedures (410 open Bankart, 163 Latarjet-Bristow, and 2291 arthroscopic Bankart) included. There was no significant difference with regard to age ( P = .11), body mass index ( P = .17), American Society of Anesthesiologists class ( P = .423), or CCI ( P = .479) for each group. The Latarjet-Bristow procedure had the highest overall complication rate (5.5%) compared with open (1.0%) and arthroscopic (0.6%) Bankart repairs. The Latarjet-Bristow procedure had significantly longer mean operative times ( P < .001) in addition to the highest 30-day return rate to the operating room (4.3%; 95% confidence interval, 1.2%-7.4%). Smoking status was an independent predictor of a postoperative complication ( P = .05; odds ratio, 8.0) after Latarjet-Bristow. Conclusion: Surgical intervention for anterior shoulder instability has a low rate of complication (arthroscopic Bankart, 0.6%; open Bankart, 1.0%; Latarjet-Bristow, 5.5%) in the early postoperative period, with the most common being surgical site infection, deep vein thrombosis, and return to the operating room.